Sample disturbances due to removal of confining pressure in laminated clay. Issue 5 (11th October 2020) - Moore, Laura; Pandey, Pratiksha; Sivakumar, Vinayagamoorthy; Donohue, Shane; Mackinnon, Pauline; Doherty, Ciaran
Abstract : Sample disturbances in laminated soils may be caused by several factors, including water movement between the clay and sand layers upon removal of overburden pressures. The research reported in this article examined the impact of this water movement on various geotechnical parameters. Samples of kaolin with laminations were formed, subjected to isotropic consolidation and subsequently sheared under undrained conditions. Further tests were carried out in which the samples were isotropically unloaded after consolidation and isotropically reloaded under undrained conditions, followed by undrained shearing. Tests were also carried out to examine the impact of unloading/reloading on the yield stress and small-strain stiffness. The results showed that the isotropic unloading/reloading process under undrained conditions led to reductions in the undrained shear strength, small-strain stiffness and yield stresses. Comparative tests carried out on unlaminated samples showed that the unloading/reloading process had a marginal impact on the above mentioned geotechnical properties.